PENGEMBANGAN MEDIA PEMBELAJARAN BOARD GAME “PROBABILITY QUEST” PADA MATERI PELUANG UNTUK SISWA KELAS X DI SMA TERPADU WIRA BHAKTI GORONTALO - Nurdian Siama; Syamsu Qamar Badu; Khardiyawan A.Y. Pauweni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by students' difficulties in understanding mathematical concepts, specifically the probability topic, which is often considered abstract and tedious, combined with the school's policy of limiting digital device usage during class hours. As a solution, this study aims to describe the development process of a non-digital learning tool in the form of the "Probability Quest" board game for tenth-grade high school students that is valid, feasible, and practical. The methodology employed was Research and Development (R&D) using the 4D development model, which includes the Define, Design, Develop, and Disseminate stages. The trial subjects involved 27 students from class X-4 at SMA Terpadu Wira Bhakti Gorontalo. Data collection instruments consisted of validation sheets, readability questionnaires, and response questionnaires to measure the media's feasibility and practicality. The results of the study indicated that the "Probability Quest" board game learning media met the criteria for being highly feasible and highly practical. This is demonstrated by: (1) the student readability questionnaire analysis, which scored 91.5% in the highly feasible category; (2) the mathematics teacher response questionnaire analysis, which achieved 93% in the highly practical category ; and (3) the student response questionnaire analysis during the field trial, which reached 98.98% in the highly practical category. In conclusion, the "Probability Quest" board game is declared valid, feasible, and practical to be used as an alternative, engaging, and interactive innovation for non-digital mathematics learning